2017
DOI: 10.1099/mic.0.000419
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new regulatory genes involved in the pathogenic functions of the rice-pathogenic bacterium Burkholderia glumae

Abstract: Burkholderia glumae is an emerging plant-pathogenic bacterium that causes disease in rice in several of the major rice-producing areas throughout the world. In the southern United States, B. glumae is the major causal agent of bacterial panicle blight of rice and has caused severe yield losses in recent decades. Despite its importance, few management options are available for diseases caused by B. glumae, and knowledge of how this pathogen causes disease is limited. In an effort to identify novel factors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…The transcriptomic analysis suggested that the toxoflavin biosynthesis and transport genes and the extracellular protease gene prtA were negatively and positively regulated by tepR and the tofI/tofR QS system, respectively. This is in line with the drastic increase and decrease of toxoflavin production and extracellular protease activity in ΔtepR and ΔtofI-tofR, respectively, compared with the wild type, B. glumae 336gr-1 (Chen et al, 2012;Melanson et al, 2017;Lelis et al, 2019). signal C 8 -HSL and its cognate receptor TofR form a complex to activate the expression of toxJ, a LuxR family transcriptional regulator gene, which further induces the toxoflavin biosynthesis/transport genes via ToxR (Kim et al, 2004(Kim et al, , 2009.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The transcriptomic analysis suggested that the toxoflavin biosynthesis and transport genes and the extracellular protease gene prtA were negatively and positively regulated by tepR and the tofI/tofR QS system, respectively. This is in line with the drastic increase and decrease of toxoflavin production and extracellular protease activity in ΔtepR and ΔtofI-tofR, respectively, compared with the wild type, B. glumae 336gr-1 (Chen et al, 2012;Melanson et al, 2017;Lelis et al, 2019). signal C 8 -HSL and its cognate receptor TofR form a complex to activate the expression of toxJ, a LuxR family transcriptional regulator gene, which further induces the toxoflavin biosynthesis/transport genes via ToxR (Kim et al, 2004(Kim et al, , 2009.…”
Section: Discussionsupporting
confidence: 66%
“…tepR, encoding a bEBP, was recently identified as a negative regulator of toxoflavin, the most important virulence factor of B. glumae (Melanson et al, 2017). Toxoflavin and other known virulence factors of B. glumae are under the tight regulation of the tofI/tofR QS system (Kim et al, 2004(Kim et al, , 2007Devescovi et al, 2007;Lelis et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the pathogenicity of B. multivorans ATCC 17616 in the Galleria mellonella larvae model of infection is apparently not regulated by the ScmR homologue LdhR (37), the loss of ScmR in both B. thailandensis E264 and B. pseudomallei Bp82 resulted in hypervirulence toward the model host C. elegans (26, 34). In addition, Melanson et al (38) demonstrated that the rice pathogen B. glumae 336gr-1 ScmR homologue, called NtpR, is a negative regulator of toxoflavin production, which is considered the primary virulence factor of B. glumae , suggesting that similarly to the B. thailandensis E264 and B. pseudomallei Bp82 ScmR homologues, NtpR influences virulence. In B. thailandensis and B. pseudomallei , ScmR was proposed to modulate the infection process by repressing the biosynthesis of malleilactone (26, 34).…”
Section: Discussionmentioning
confidence: 99%